Integrasi Materi Kesantunan ke dalam Kompetensi Dasar Mata Pelajaran Bahasa Indonesia: Tinjauan Pragmatik - Suhartono Suhartono (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This research aims at identifying basic competencies (KD) at the levels of elementary school (SD), junior high school (SMP), and high school (SMA) viewed from the politeness material. To achieve the goal, data in the form of KD in Indonesian language subjects at SD, SMP, and SMA extracted from the documents of the Decree of Education Ministry No 37 of 2018 Core Competencies and Basic Competencies of Subjects in the 2013 Curriculum were evaluated. Data were collected using documentation techniques, while data in the form of scores from the validation results were obtained from two expert validators. The collected data were analyzed using the Miles and Huberman (1984) flow technique. Results show scores of validation of SD, SMP, and SMA were 9, 9. The score of KD of each school was 8 respectively in core competencies (KI) III (knowledge domain) and KI IV (skills domain) which could potentially be integrated with politeness material. The integration which is done by adding the word "polite" to the competency achievement indicator (GPA) which is the result of KD development is considered valid by two expert validators with a mean score of 3.85 and 4.00, respectively. The existence of the word "polite" in the GPA has the consequence that the word "santun" is included in some of the learning objectives, politeness material is developed explicitly in textbooks and taught in classroom learning, and polite language competence is part of the assessment criteria.